Implementasi Tri Hita Karana Melalui Media E-Learning Pada Kelas X Di SMA Negeri 3 Denpasar - Bayu Arta Wijaya, Anak Agung Ngurah (Jayapangus Press, 2022)
Humans as individual, social and religious creatures must be balanced in order to create a harmonious life. Hindus in Bali know Tri Hita Karana as a teaching to create a harmonious life. Tri Hita Karana is introduced in formal education. Due to the endless pandemic, face-to-face learning has been canceled. However, learning is still carried out using an e-learning system. SMA Negeri 3 Denpasar applies e-learning to support the learning process. E-learning is applied to one of the subjects of Hindu Religious Education by adopting the school's vision and mission as a reference. In this study, we will discuss the process of implementing Tri Hita Karana through e-learning media in class X at SMA Negeri 3 Denpasar, obstacles to implementing Tri Hita Karana through e-learning media in class X at SMA Negeri 3 Denpasar, efforts made to overcome obstacles implementation of Tri Hita Karana through e-learning media in class X at SMA Negeri 3 Denpasar. The process of implementing Tri Hita Karana through e-learning media can be seen through the learning strategies used, the implementation process, and the evaluation of learning. In addition, there are also obstacles arising from the implementation of Tri Hita Karana through e-learning media including obstacles based on the implementation of Tri Hita Karana, constraints based on the use of e-learning media, and constraints based on students' backgrounds. Thus, of course there must be an effort to overcome the implementation of Tri Hita Karana through e-learning media including internal and external factors.